2011
DOI: 10.1007/s10815-011-9579-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoic acid on maturation of immature mouse oocytes in the presence and absence of a granulosa cell co-culture system

Abstract: Purpose Evaluation of the all-trans retinoic acid (t-RA) effects on in vitro maturation (IVM) and in vitro fertilization (IVF) of immature mouse oocytes in the presence and absence of granulosa cell monolayer. Methods Denuded oocytes isolated from mice ovaries and matured in IVM medium alone (Control I), IVM medium in the presence of granulosa cells (Control II), IVM medium with t-RA (Experimental I) and IVM medium simultaneously with t-RA and granulosa cells (Experimental II). After 24 h, matured oocytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…The beneficial effects of RA on in vitro oocyte maturation and embryo development have been previously described (Almiñana et al 2008;Vahedi et al 2009;Chiamenti et al 2010;Tahaei et al 2011). However, there are no reports about the effects of t-RA on the developmental ability of goat oocytes and cumulus cell viability.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The beneficial effects of RA on in vitro oocyte maturation and embryo development have been previously described (Almiñana et al 2008;Vahedi et al 2009;Chiamenti et al 2010;Tahaei et al 2011). However, there are no reports about the effects of t-RA on the developmental ability of goat oocytes and cumulus cell viability.…”
Section: Discussionmentioning
confidence: 87%
“…Vitamin A is one of the fat-soluble vitamins and is generally believed to regulate cell growth and differentiation, tissue function, and support both male and female reproduction as well as embryonic development (Clagett-Dame & Knutson 2011). As an active metabolite, t-RA has multiple effects on reproduction, such as stimulating initiation of meiosis of germ cells (Li & Margaret 2009), regulating gap junction intercellular communication and improving bovine and mouse oocyte maturation in vitro (Vahedi et al 2009;Tahaei et al 2011). Many studies have elucidated that RA enhances oocyte competence through multiple mechanisms, including oxidative-stress protection (Guerin et al 2001), follicle-stimulation hormone / luteinizing hormone (FSH/LH) receptor expression (Minegishi et al 2000) and reduction in oocyte tumor nectrosis factor (TNF)-α (Deb et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crabp2 encodes the cellular retinoic acid binding protein 2. Retinoic acid contributes to oocyte maturation (Bowles and Koopman, 2010; Tahaei et al, 2011). Nppc encodes natriuretic peptide precursor C that, upon proteolytic cleavage, generates C-type natriuretic peptide that functions as the agonist of the guanylyl cyclase membrane receptor NPR2.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoid homeostasis plays a key role in female reproduction, and it has been reported that retinoid signalling can initiate the meiosis of germ cells in mammalian foetal ovaries as well as promote ovarian steroidogenesis (Bagavandoss & Midgley, 1987;Wickenheisser et al, 2005), oocyte maturation (Ikeda, Kitagawa, Imai, & Yamada, 2005;Tahaei, Eimani, Yazdi, Ebrahimi, & Fathi, 2011), corpus luteum formation (Jiang, Li, Chen, Wang, & Zhou, 2017), and follicular development (Brown, Eberhardt, Schrick, Roberts, & Godkin, 2010;Kawai, Yanaka, Richards, & Shimada, 2016;Kipp et al, 2011). Retinol-binding protein 4 (RBP-4), which is a mediator for the systemic and intercellular transport of retinol (vitamin A), plays important roles in cellular retinol influx, efflux and exchange and is correlated with many metabolic diseases, including PCOS (Sammar, Levi, Hurvitz, & Lubzens, 2005) and insulin resistance (Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%